Insight into the occupational health among the industrial operators: a physiological and psychological approach - Xiaojun, Ho (Universiti Sains Malaysia, 2014)
This study investigated the occupational health status of agricultural and ship maintenance operators via physiological and psychological approach. Physiological health status was examined in terms of Body Mass Index. Physical Workload Index Questionnaire (PWIQ), Rapid Entire Body Assessment (REBA), changes in physiological parameters. Physiological Stress Index (PSI), and Heat Index. Psychological health status of workers was investigated using Negative Act Questionnaire-Revised. Depression. Anxiety and Stress Scales-21. General Health Questionnaire-12, and WHO Quality of Life (QoL) - Brief Version. The physiological and psychological status of agricultural and ship maintenance industrial operators were quantified by prevalence of co-morbidity conditions (37.0%), hypertension (27.0%). obesity (14.0%). PWIQ (mean = 17.4. SD = 7.0). REBA (mean = 4.4. SD = 7.9). PSI (mean =1.1. SD = 0.6). prevalence of bullying (83.0%), depression (12.0%). anxiety (25.0%). stress (6.0%). predicted commo mental disorder cases (2.0%). and poor QoL (environmental = 19%. psychological = 18%. physical = 12%. social relationship = 9%). The prevalence of co-morbidity conditions, predicted common mental disorder cases, poor physical QoL. and psychological QoL were higher among agricultural operators (46.3%. 3.7%. 14.8%. and 16.7%) as compared to ship maintenance workers (26.1%. 0.5%. 11.1%. and 17.4%). However, ship maintenance workers were subjected to higher physiological and psychological strain as indicated by mean scores of PWIQ and REBA, and the prevalence of bullying experience, depression, anxiety and stress, and poor environmental QoL (mean = 22.8, mean = 6.7, 93.5%. 13.0%, 26.1%. 8.7% and 17.4%) as compared to agricultural industrial operators (mean = 12.7. mean = 2.5. 74.1%. 11.1%. 24.1%. 3.8%. and 16.7%). This study also found that work related factors and individual factors showed greater impact on physiological and psychological health as compared to individual factors as the occupation will determine the exposure of hazard on an individual. The physiological and psychological health statuses of the workers were inter-correlated. The health statuses of workers need to be further improved for the benefit of the workers. companies, and industries.